Maternal health in Sub-Saharan Africa : are national user fee waiver policies for intrapartum services the key to reducing maternal mortality? A quantitative cross-country comparison - Sabine Damerow (2023)
Background: The provision of an effective facility-based intrapartum care strategy targeted at all intrapartum women is seen as a priority measure to substantially reduce the burden of maternal mortality, which is currently a major global health concern that especially affects the Sub-Saharan African (SSA) region. Intending to increase access to these services, numerous SSA countries have implemented national user fee waiver policies for facility-based intrapartum care. Evidence regarding the impact of these policies on the utilisation of the corresponding services is scarce and entirely lacking for maternal health outcomes. Therefore, this thesis aims to evaluate differences in related utilisation rates (UR) and maternal mortality ratios (MMR) between SSA countries with national user fee waiver policies for facility-based intrapartum care and those without. Methods: Using a quantitative cross-country comparison, an intervention group of SSA countries that apply national user fee waiver policies for facility-based intrapartum care (n=15) was compared with a control group of SSA countries without equivalent policies (n=6). Data were extracted from the World Health Organization’s Policy Surveys, Demographic and Health Surveys, and the World Bank’s World Databank. As primary outcome measures, URs of facility deliveries and caesarean sections and estimated MMRs were used. Results: URs of facility deliveries of the two groups differed significantly. The intervention group’s median accounted for 59.4% and the control group’s for 79.0% of all live births (p=0.022). Differences in URs of caesarean sections and MMRs, however, were not significant. The intervention and control group’s medians regarding URs of caesarean sections accounted for 4.3% and 5.5% of all live births respectively and regarding MMRs for 398 and 590 maternal deaths per 100,000 live births respectively. Conclusions: On average, findings revealed lower URs and MMRs in the intervention group. A number of hypotheses could explain the results. These include possible successful needsbased prioritisations of women at risk in the intervention group, a corresponding smaller share of risk groups or particularly effective alternative services. Adverse impacts of facility-based intrapartum care and a resulting positive correlation between URs and MMRs, e.g. due to medical malpractice or hospital-acquired infections, might be a further explanation. Additional research is necessary to prove these hypotheses.